INVESTIGATING THE EFFECT OF THINK TALK WRITE (TTW) STRATEGY ON STUDENTS’ NARRATIVE WRITING ACHIEVEMENT: A QUASI-EXPERIMENTAL STUDY - Wiwik Alwiah (Pusat Kajian dan Pengembangan Publikasi Ilmiah (PKPPI) Institut Agama Islam Hamzanwadi Nahdlatul Wathan Lombok Timur, 2025)
This study aimed to investigate whether the application of the Think-Talk-Write (TTW) strategy could enhance the writing ability of second-year students at MAN Polman. This research employed a quasi-experimental design. The population consisted of second-year students at MAN Polman in the academic year 2012/2013. A sample of 40 students was selected from two classes using a cluster random sampling technique, and was then divided into two groups: an experimental group and a control group. The primary difference between the two groups lay in the teaching techniques used during the treatment. While the experimental group was taught using the TTW strategy, the control group received instruction through conventional methods. The instrument used in this study was a narrative writing test. Based on the data collected, the results showed that the post-test scores of the experimental group were significantly higher than those of the control group. This was demonstrated by the mean post-test score of the experimental group (77.85), which was higher than that of the control group (51.65). Moreover, the t-test value (3.58) exceeded the critical value of the t-table (2.042), indicating a statistically significant difference.